Towards integrating social dynamics into climate economic scenarios literature review - Simon Barth (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2022)
Climate policy options are usually elaborated scientifically by Integrated Assessment Models that combine the economic system, the energy system and the climate system in one comprehensive framework. Most of them follow a neo-classical economic paradigm and calculate cost-efficient technological transformation pathways of the energy system. Critique has grown that the real-world problem is more complex especially with regard to the dynamics reigning in human societies. These should be considered in the models in order to derive effective policy recommendations. This literature review presents and structures a list of publications making first steps into this direction, either by delivering promising methodological suggestions, by reporting evidence on social dynamics or by presenting first model integrations. By this, the paper illuminates the scientific challenge of integrating social dynamics into climate economic scenarios and builds a knowledge basis for future research endeavors.
Keywords: 330; climate economics; social dynamics; energy transitions; integrated assessment